Literasi Digital Santri Milenial: Studi Kasus Pondok Pesantren Tahfidzul Quran Al-Jihadul Chakim Mojokerto - Abdulloh Hamid; Al Watsiqoh, Mila Haibatu; Mohd Kamarulnizam bin Abdullah; Moh. Hafiyusholeh (State Islamic Institute of Madura, 2024)
Pesantren or Islamic Boarding Schools is a type of classical educational institution that still exis nowadays. As time goes by, Pesantren always has formal educational institutions in the form of madrasah. Students who live in pesantren are identified as students who do not know the advancement of technology. Moreover, not being allowed to use cell phones in the pesantren area is being another trigger. The purpose of this study is to find the related approach of MTs Al-Jihadul Chakim in facilitating their students in digital literacy. This study uses qualitative methods, focusing on digital literacy. The results of this study found that MTs Al-Jihadul Chakim as a pesantren-based madrasah provides programs and facilities for its students to have digital literacy skills. The form of those approaches are programs such as ICT-based learning, assistance in managing social media wisely, coaching graphic design skills, and photos/videography program.